2022
DOI: 10.3389/fpubh.2022.997716
|View full text |Cite
|
Sign up to set email alerts
|

To assess and compare the mental health of current-left-behind children, previous-left-behind children with never-left-behind children

Abstract: The study's goal was to compare the mental health of children who are now left-behind (current-LBC) to children who have never been left-behind (never-LBC). Recruits were culled from rural Chinese schools. The Strengths and Difficulties Questionnaire (SDQ) and the Parent-Adolescent Communication Scale (PACS) were used to examine participants' migratory status, mental health, and parent-child communication (PACS). A total of 2,000 current-, 500 previous-, and 300 never-LBCs in had complete data readily accessib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…In this study, the total score of SCL-90 of left-behind children during the pandemic was observed to be higher than the national norm (130.02 ± 33.63), 16 indicating the overall poor mental health status of left-behind children during the pandemic, and the results are consistent with those of previous studies. 11 , 12 , 17 Conversely, the SCL-90 score of left-behind children after the pandemic was lower than the national norm, which indicated that the mental health of left-behind children improved significantly after the pandemic compare with that during the pandemic. This result may be attributed to the cancellation of the closed stay policy after the pandemic, recovery of traffic roads, parents of left-behind children returning to their hometown, and the left-behind children feeling more loved and having a sense of security and trust compared with that during the pandemic.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In this study, the total score of SCL-90 of left-behind children during the pandemic was observed to be higher than the national norm (130.02 ± 33.63), 16 indicating the overall poor mental health status of left-behind children during the pandemic, and the results are consistent with those of previous studies. 11 , 12 , 17 Conversely, the SCL-90 score of left-behind children after the pandemic was lower than the national norm, which indicated that the mental health of left-behind children improved significantly after the pandemic compare with that during the pandemic. This result may be attributed to the cancellation of the closed stay policy after the pandemic, recovery of traffic roads, parents of left-behind children returning to their hometown, and the left-behind children feeling more loved and having a sense of security and trust compared with that during the pandemic.…”
Section: Discussionmentioning
confidence: 86%
“…5 Mental health of left-behind children is in poor state. 6 Studies have consistently shown that left-behind children are more likely to have mental health problems than non-left-behind children, 7–10 and these problems are manifested as high levels of emotional symptoms, behavioral difficulties, and learning difficulties 11 such as depression, self-injurious behavior, and game addiction. 12 Left-behind children aged 7–12 years are more likely to experience obsessive-compulsive disorder, interpersonal sensitivity, anxiety, hostility, paranoia, and other problems than other age groups.…”
Section: Introductionmentioning
confidence: 99%
“…This can lead to a feeling of discomfort and dissatisfaction in their lives, as they believe that others are isolating and discriminating against them and that they are not trusted and accepted by others (Chen and Chang, 2012). The main effects model states that perceiving low social support affects the psychological state of individuals, resulting in anxiety, other psychological problems and the fears of losing existing interpersonal relationships and feelings of insecurity (Peirce et al, 1996;Yang, 2022). This ultimately leads to low levels of subjective well-being and satisfaction with family, friendships, and school.…”
Section: Discussionmentioning
confidence: 99%
“…Existing literature indicates that such demographic-specific migration has already led to a large number of left-behind children, who are raised with limited or no parental supervision (Gao et al, 2010). Though they may receive care from grandparents and remittances from migrant parents, these children often experience loneliness, mental instability and other social challenges (Zhang, 2013;Growing Home, 2016;Wu, Song, and Huang, 2016). Assessing the broader socioeconomic consequences of these migration patterns represents a fertile avenue for future research.…”
Section: Discussionmentioning
confidence: 99%